Marker patterning: a spatially resolved method for tuning the wettability of PDMS. Issue 73 (2nd October 2017) - Bodin-Thomazo, N.; Malloggi, F.; Guenoun, P.
Abstract : This article presents a marker patterning method where a permanent ink is used as a masking layer. During plasma oxidation, the PDMS surfaces are protected leading to a simple and easy wettability patterning. Abstract : Versatile, inexpensive and easy to use, PDMS has become a very common material, especially in the field of microfluidics. Intrinsically hydrophobic, it can be made hydrophilic by exposure to oxygen plasma. For some applications, wettability patterning of the PDMS surface is needed, in particular for the formation of monodisperse multiple emulsions. In this work we present an easy and spatially resolved way to tune the wettability of PDMS. Patterning is achieved without tedious or complicated surface processing by simply drawing the desired pattern onto the PDMS surface using the permanent ink of a marker as a masking layer. The microfluidic device is then exposed to oxygen plasma prior to bonding and flushed with ethanol when bonded. The parts of PDMS which are protected remained hydrophobic whereas unprotected surfaces are oxidized. The process is demonstrated by forming W/O/W emulsions in a controlled manner.